Delayed application of N fertilizer mitigates the carbon emissions of pea/maize intercropping via altering soil microbial diversity - Xu, Ke; Hu, Falong; Fan, Zhilong; Yin, Wen; Niu, Yining; Wang, Qiming; Chai, Qiang (Frontiers in Microbiology, 2022)
Strategies to reduce carbon emissions have been a hotspot in sustainable agriculture production. The delayed N fertilizer application had the potential to reduce carbon emissions in pea (Pisum sativum L.)/maize (Zea mays L.) intercropping, but its microbial mechanism remains unclear. In this study, we investigated the effects of delayed N fertilizer application on CO2 emissions and soil microbial diversity in pea/maize intercropping. The soil respiration (Rs) rates of intercropped pea and intercropped maize were decreased by 24.7% and 25.0% with delayed application of N fertilizer, respectively. The total carbon emissions (TCE) of the pea/maize intercropping system were also decreased by 21.1% compared with that of the traditional N fertilizer. Proteobacteria, Bacteroidota, and Chloroflexi were dominant bacteria in pea and maize strips. Heatmap analysis showed that the soil catalase activity at the pea flowering stage and the soil NH+ 4-N at the maize silking stage contributed more to the variations of bacterial relative abundances than other soil properties. Network analysis demonstrated that Rs was positively related to the relative abundance of Proteobacteria and Bacteroidota, while negatively related to the relative abundance of Chloroflexi in the pea/maize intercropping system. Overall, our results suggested that the delayed application of N fertilizer combined with the pea/maize intercropping system altered soil bacterial community diversity, thereby providing novel insights into connections between soil microorganisms and agricultural carbon emissions.